2014
DOI: 10.1080/03235408.2014.882541
|View full text |Cite
|
Sign up to set email alerts
|

Control of nematode disease of egg plant (Solanum aethiopicum) using manure

Abstract: Pot experiment was conducted in the year 2010 and repeated in 2011 to examine the effects of organic manure (poultry, cow dung and domestic waste) and inorganic manure (NPK 15:15:15) on the yield, soil and root population of Meloidogyne incognita-infected Ethiopian egg plant Solanum aethiopicum in a greenhouse at Kabba college of agriculture, Ahmadu Bello University, Kabba, Nigeria. Each of the organic manure was applied as soil amendment at the rate of 5t/ha and the inorganic fertiliser (NPK) was applied at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…Recently, Ismail and co‐workers reported on the use of cress ( Eruca sativa ), castor ( Ricinus communis ) and linseed ( Linum usitatissimum ) against M. arenaria in potato fields . Organic manure (poultry, cow dung and domestic waste) used for the control of M. incognita on Ethiopian eggplant ( Solanum aethiopicum ) improved yield in greenhouse pot experiments . Stirling suggested that conventional vegetable farming systems could be improved by annually incorporating commercially available organic amendments, or by mulching biomass from rotation crops onto the bed surface well before the vegetable crop is to be planted, or by leaving the bed undisturbed and covering those residues with plastic .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Ismail and co‐workers reported on the use of cress ( Eruca sativa ), castor ( Ricinus communis ) and linseed ( Linum usitatissimum ) against M. arenaria in potato fields . Organic manure (poultry, cow dung and domestic waste) used for the control of M. incognita on Ethiopian eggplant ( Solanum aethiopicum ) improved yield in greenhouse pot experiments . Stirling suggested that conventional vegetable farming systems could be improved by annually incorporating commercially available organic amendments, or by mulching biomass from rotation crops onto the bed surface well before the vegetable crop is to be planted, or by leaving the bed undisturbed and covering those residues with plastic .…”
Section: Discussionmentioning
confidence: 99%
“…42 Organic manure (poultry, cow dung and domestic waste) used for the control of M. incognita on Ethiopian eggplant (Solanum aethiopicum) improved yield in greenhouse pot experiments. 43 Stirling suggested that conventional vegetable farming systems could be improved by annually incorporating commercially available organic amendments, or by mulching Pest Manag Sci 2015; 71: 1099-1105 biomass from rotation crops onto the bed surface well before the vegetable crop is to be planted, or by leaving the bed undisturbed and covering those residues with plastic. 44 Organic amendments with Brassica species in combination with solarisation can sometimes be used as an alternative to conventional nematicides.…”
Section: Discussionmentioning
confidence: 99%
“…They found that these biocontrol agents were effective in suppressing M. incognita and could be used as safe agents for sustainable environment. Abolusoro et al (2013) reported that organic manure (poultry, cow dung, domestic waste) and inorganic fertilizer (NPK 15:15:15) were effective in suppressing M. incognita soil and root populations, reducing gall index of the treated eggplants compared with the control in a greenhouse Mokbel and Alharbi (2014) found that Pseudomonas fluorescens, B. thuringiensis, Bacillus subtilis, and S. marcescens each alone or in a combination resulted in 50.5-90.3% restrained M. javanica egg-hatch and J 2 activity and caused 56.5-86.8% decrease in egg-masses/eggplant root system, root galls,, and 50.9-73.7% rise in the shoot and root dry weights of eggplant. Also, Arthrobotrys conoides, Purpureocillium lilacinus, A. oligospora, and Saccharomyces cerevisiae induced considerable reductions (69.5-89.5%) in galls and egg-masses/root system, and led to 53.7-60.9% enhancement in shoot and root dry weights of eggplant.…”
Section: Further Integrated Applicationmentioning
confidence: 99%
“…Using organic amendments such as composts, agricultural and other industrial wastes, crop residues and plant derivatives to control plant-parasitic nematodes has been reported in voluminous reports (Rahman et al, 2011;Abolusoro et al, 2013;Rizvi et al, 2018). Rizvi et al (2018) indicated that organic soil amendments increased plant growth, biomass,chlorophyll and nutrient status(N, P and K).…”
Section: Introductionmentioning
confidence: 99%